ANALYSIS OF CUSTOMER COMPLAINT MANAGEMENT ON THE INDIHOME - Erick Yusuf Ardiyanto; Agustin Amborowati (Bajang Institute, 2024)
One of the internet providers is PT Telekomunikasi Indonesia, Tbk with its product IndiHome. With so many people subscribing to IndiHome, it does not rule out the possibility of network disruptions. According to Daryanto (2021:34) revealed that complaints are complaints or submissions of dissatisfaction with discomfort, irritation, and anger over service/products. This study aims to analyze the implementation of complaint management on IndiHome network disruptions by PT Telkom Akses Solo. The research design used by the author is a case study with a descriptive method. Then the author used research data from interviews and observations regarding the management of complaints of IndiHome customer network disruptions. In addition, mendescripting problems and solutions to problems experienced by PT Telkom Akses Solo when managing complaints of customer network disruptions. Based on the results of the study, the treatment provided is quite good and in accordance with the established procedures. Then, PT Telkom Akses Solo can maintain fast service so that customers are loyal and do not move to competitors. In the use of technology, to report network disturbances through the myIndiHome application, then education can be done to customers even more massively about the use of the myIndiHome application.